The influence of three diphenylpyran isomer co-sensitizers with different sterical structures on N719-based dye sensitized solar cells. Issue 71 (7th December 2020) - Wang, Xinxin; Hang, Xiuhua; Bolag, Altan; Yun, Wu; Bao, Tana; Ning, Jun; Alata, Hexig; Ojiyed, Tegus
Abstract : This work applied three isomers with different spatial geometries as co-sensitizers to enhance N719 -based dye sensitized solar cells. Abstract : Aiming to explore the relationship between the molecular structure and photovoltaic performance, three pyran isomer dyes DO, DM and DP were synthesized and applied as a co-sensitizer with N719 dye in dye-sensitized solar cells (DSCs). These sensitizers were investigated by theoretical calculation, UV-vis absorption spectroscopy and cyclic voltammetry measurement to understand their structure, optical and electrochemical properties. The DSC devices based on N719 and the co-sensitizers were characterized using I – V tests, incident photon-to-current conversion efficiency and electrochemical impedance spectroscopy measurements. As compared to the standard N719 -based DSCs, the co-sensitization system of N719 and DM with the most sterical structure exhibited an enhancement of the power conversion efficiency (PCE) by 18% from 7.60% to 8.96%. Both the short-circuit photocurrent density ( J sc ) and open-circuit voltage ( V oc ) of the co-sensitized systems were increased resulting from the better maintained N719 dye loading amount on TiO2 as well as the prevention of dye aggregation. Co-sensitization of the DO molecule with less steric hindrance reduced the desorbed N719 dye amount by half leading to a decline of the photo-harvesting ability and photocurrent generation in DSCs.